Synthesis and Characterisation of Bio-based Epoxy/Clay Nanocomposites - Salam, Haipan (Curtin University, 2017)
The thesis focuses on investigating the substitution of conventional epoxy with a bio-based epoxy constituent to achieve bionanocomposites with sustainable bio-based content and optimal mechanical properties. Taguchi design of experiments was employed to determine the preferred combination of factors in manufacturing bionanocomposites. Mechanical, thermal and biodegradability properties, as well as morphological structure were observed to investigate the effect of clay and bio-based content. Theoretical models were studied in successfully predicting mechanical properties of bioepoxy/clay nanocomposites.